The milking hall at the State Farm. Supplement to bulletin no. 112, 1961 of the Bulgarian News Agency (p.12) (1961)
The milking hall at the State Farm. Supplement to bulletin no. 112, 1961 of the Bulgarian News Agency (p.12).